Research Progress of Pancreas-Related Microorganisms and Pancreatic Cancer - Zhang, Wenqing; Zhang, Kunpeng; Zhang, Peng; Zheng, Juanjuan; Min, Congcong; Li, Xiaoyu (Frontiers in Oncology, 2021)
Known as "the king of cancers", pancreatic cancer is one of the most common digestive system cancers. Early diagnosis is difficult owing to the lack of specific symptoms and reliable biomarkers. The cause of pancreatic cancer remains ambiguous. Smoking, drinking, new-onset diabetes, and chronic pancreatitis have been proven to be associated with the occurrence of pancreatic cancer. In recent years, a large number of studies have clarified that a variety of microorganisms colonized in pancreatic cancer tissues are also closely related to the occurrence and development of pancreatic cancer, and the specific mechanisms include inflammatory induction, immune regulation, metabolism, and microenvironment changes caused by microbial malnutrition. The mechanism of action of the pancreatic colonized microbiome in the tumor microenvironment, as well as immunotherapy approaches require further study in order to find more evidence to explain the complex relationship between the pancreatic colonized microbiome and PDAC. Relevant studies targeting the microbiome may provide insight into the mechanisms of PDAC development and progression, improving treatment effectiveness and overall patient prognosis. In this article, we focus on the research relating to the microorganisms colonized in pancreatic cancer tissues, including viruses, bacteria, and fungi. We also highlight the microbial diversity in the occurrence, invasion, metastasis, treatment, and prognosis of pancreatic cancer in order to elucidate its significance in the early diagnosis and new therapeutic treatment of pancreatic cancer, which urgently need to be improved in clinical practice. The elimination or increase in diversity of the pancreatic microbiome is beneficial for prolonging the survival of PDAC patients, improving the response to chemotherapy drugs, and reducing tumor burden. The colonization of microorganisms in the pancreas may become a new hotspot in the diagnosis and treatment of pancreatic cancer.